2004
DOI: 10.1093/ndt/gfh189
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal mitochondrial function and muscle wasting, but normal contractile efficiency, in haemodialysed patients studied non-invasively in vivo

Abstract: The relationships to urea reduction ratio reflect the effect of muscle mass on dialysis efficiency, rather than direct effects on muscle CSA or metabolism. The relationship between PCr recovery and calf CSA suggests a role for the mitochondrial defect, whatever its cause, in the development of muscle wasting, although a common cause (e.g. physical inactivity) for both abnormalities cannot be ruled out.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 18 publications
4
49
0
4
Order By: Relevance
“…Entretanto, representam forma de intervenção de complicações da doença renal (16) , visto que alterações na função pulmonar são comuns na disfunção renal (24) . Nos pacientes com IRA, a musculatura esquelética respiratória apresenta diminuição das propriedades de força, ocasionando déficit ventilatório, o que contribui para diminuição da capacidade pulmonar (27) . O uso de drogas vasoativas apresenta relação significante com o desenvolvimento de IRA, constituindo fator intensamente negativo.…”
Section: Discussionunclassified
“…Entretanto, representam forma de intervenção de complicações da doença renal (16) , visto que alterações na função pulmonar são comuns na disfunção renal (24) . Nos pacientes com IRA, a musculatura esquelética respiratória apresenta diminuição das propriedades de força, ocasionando déficit ventilatório, o que contribui para diminuição da capacidade pulmonar (27) . O uso de drogas vasoativas apresenta relação significante com o desenvolvimento de IRA, constituindo fator intensamente negativo.…”
Section: Discussionunclassified
“…Of the remaining case-control studies, seven 15,[36][37][38][39][40][41] included participants with chronic renal disease not on HD and with comorbidities (clinical evidence of polyneuropathy, varying degrees of paresis, myopathy, renal bone disease, cerebrovascular accident, diabetes mellitus, peripheral vascular disease, etc. ); four included male participants only; [42][43][44][45] and five [46][47][48][49][50] did not provide adequate description of the participants included in the study. Inclusion of participants with clinical evidence of neuromuscular involvement, wide age ranges, and comorbidities that could contribute to neuromuscular impairment suggested possible selection bias that could confound the outcomes of these studies.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…The finding of myopathic changes in another sub-group by Blank et al 61 is supported by similar findings in two studies 46,48 that did not suggest (implicitly or otherwise) the presence of muscle weakness in their participants. 43,47 investigated the finger flexors. Specific differences among these four studies could not be clearly identified to establish why the cytosolic Pi was comparable to controls; they investigated the same muscles (calf and finger flexors) as the group of studies reporting increased cytosolic Pi, with the exception of the dorsiflexor muscle.…”
Section: Electrophysiological Characteristicsmentioning
confidence: 99%
“…Some authors 10 who have studied the involvement of uremia in the diaphragm have concluded that loss of strength occurs through severe uremia. The ventilatory deficit due to this impairment in respiratory muscles, combined with other lung tissue impairments, compromises the functioning of this system, thereby contributing towards decreased lung capacity 11,12 .…”
Section: Introductionmentioning
confidence: 99%